Factors Contributing To The Spread Of Asthma, Respiratory Diseases, Allergies, And Related Risk Factors (The Review of Diabetic Studies, 2024)
This growing burden of asthma and allergic disorders in Saudi Arabia is an important public health issue, but a thorough appreciation of the exact, manipulable environmental risk determinants to this phenomenon in the local urban environment is a knowledge gap. This research was thus in a bid to establish the prevalence of these conditions and measure the independent relationships of the key exposures, including culturally common practices, to inform specific interventions. The study was a cross-sectional study done on a multi-stage stratified random population of 750 adults in Riyadh, Jeddah, and Dammam. The results of health outcomes, environmental exposures, and lifestyle factors were gathered through a validated questionnaire and were analyzed in terms of chi-square tests and multiple logistic regression. Asthma was diagnosed by doctors in 16.3%. Having a family history of atopy (adjusted odds ratio, AOR=4.02; 95% CI: 2.673604; p=0.001), living within 100 meters of heavy traffic (AOR=2.41; 95% CI: 1.56372; p=0.001), and being a frequent user of Bakhoor (incense) at home were significant independent risks of asthma after confounding (p=0.002). The research finds that a complex interplay of unalterable genetic susceptibility and of strong, culture-specific, environmental exposures causes the epidemiology of respiratory disease in urban Saudi Arabia. This offers a crucial evidence foundation to population health initiatives to reduce traffic-related air pollution and indoor combustion products, as well as enhancing the chronic disease management systems.